Changes in the surface of bone and acid-etched and sandblasted implants following implantation and removal - Eroglu, Cennet Neslihan; Ertugrul, Abdullah Seckin; Eskitascioglu, Murat; Eskitascioglu, Gurcan (European Journal of Dentistry, 2016)
Objective: The aim of this study was to determine whether there are any changes in the surface of bone or implant structures following the removal of a screwed dental implant. Materials and Methods: For this, six individual samples of acid-etched and sandblasted implants from three different manufacturers’ implant systems were used. They were screwed in a D1 bovine bone, and they were removed after primary stabilization. The bone and implant surfaces are evaluated with scanning electron microscope. Results: Through examination of the surfaces of the bone prior to implantation and of the used and unused implant surfaces, it was found that inhomogeneity in the implant surface can cause microcracking in the bone. Conclusions: This is attributed to the stress induced during the implantation of self-tapping implants and suggests that a tap drill may be required in some instances to protect the implant surface.
Keywords: Acid-etched and sandblasted implant; bone surface; implant removal